Frameworks for Monetary Stability : Policy Issues and Country Experiences. (International Monetary Fund, 1994)
This book, edited by Tomas J.T. Balino and Carlo Cottarelli, addresses some of the strategic issues faced by policymakers in the choice of a monetary regime. Following an overview of some of these issues, the book considers the various theoretical or practical frameworks for the implementation of monetary policy. It then focuses on how monetary policy should be implemented.